2017
DOI: 10.1111/jeb.13174
|View full text |Cite
|
Sign up to set email alerts
|

History rather than hybridization determines population structure and adaptation in Populus balsamifera

Abstract: Hybridization between species is known to greatly affect their genetic diversity and, therefore, their evolution. Also, within species, there may be genetic clusters between which gene flow is limited, which may impact natural selection. However, few studies have looked simultaneously at the influence of among-species and within-species gene flow. Here, we study the influence of hybridization between Populus balsamifera and Populus trichocarpa on population structure and adaptation in P. balsamifera. We did th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Among forest trees, the genome of Populus trichocarpa was the first to be sequenced [9]; therefore, there have been relatively more studies on its genetic information, including its genetic diversity and population structure [10,11]. In addition, similar studies have been carried out on other tree species, such as P. nigra L. [12][13][14], P. simonii [15], P. tremuloides [16], P. balsamifera [17], P. cathayana Rehd [18], P. euphratica [19], P. tomentosa [20] and P. szechuanica var. tibetica [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among forest trees, the genome of Populus trichocarpa was the first to be sequenced [9]; therefore, there have been relatively more studies on its genetic information, including its genetic diversity and population structure [10,11]. In addition, similar studies have been carried out on other tree species, such as P. nigra L. [12][13][14], P. simonii [15], P. tremuloides [16], P. balsamifera [17], P. cathayana Rehd [18], P. euphratica [19], P. tomentosa [20] and P. szechuanica var. tibetica [21].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all species show some form of genetic structure in the distribution of genetic variation. Be it a herb with an extremely limited distribution (Freville et al 2001), a widely distributed tree species (Meirmans et al 2017), or a planktonic species from the open ocean (Peijnenburg and Goetze 2013), there may be surprising genetic discontinuities across a species' range. Patterns of population structure can take many forms, from simple gradients resulting from limited dispersal to complex hierarchical patterns resulting from ecological adaptation to local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies showed that spatial separation of Populus spp. populations is governed by historical processes, mainly by events in the Pleistocene and Holocene (Keller et al, 2010;Macaya-Sanz et al, 2012;Dewoody et al, 2015;Meirmans et al, 2017;Fan et al, 2018). Therefore, the variability of P. laurifolia population structure in the Tom River basin is the subject for a further extended research.…”
Section: Discussionmentioning
confidence: 99%